2021
DOI: 10.1038/s41598-021-81057-2
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes among tuberculosis patients and its impact on tuberculosis treatment in South Asia: a systematic review and meta-analysis

Abstract: The escalating burden of diabetes is increasing the risk of contracting tuberculosis (TB) and has a pervasive impact on TB treatment outcomes. Therefore, we conducted this systematic review and meta-analysis to examine the burden of diabetes among TB patients and assess its impact on TB treatment in South Asia (Afghanistan, Bangladesh, Bhutan, Maldives, Nepal, India, Pakistan, and Sri Lanka). PubMed, Excerpta Medica Database (EMBASE), and CINAHL databases were systematically searched for observational (cross-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
53
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 101 publications
(122 reference statements)
1
53
3
Order By: Relevance
“…6,[9][10][11] The relationship between rates of sputum conversion among TB patients with diabetes or dysglycemia appears inconsistent. 9,[12][13][14][15][16] Some studies have suggested a reduced rate at 2 months (end of the intensive phase) and 6 months (end of the treatment) 9,12 while others have shown no relationship between diabetes and sputum conversion rate at the end of the secondmonth. 14,17 More data are needed to help ascertain the impact of dysglycemia on the sputum conversion rate among TB patients.…”
Section: Introductionmentioning
confidence: 99%
“…6,[9][10][11] The relationship between rates of sputum conversion among TB patients with diabetes or dysglycemia appears inconsistent. 9,[12][13][14][15][16] Some studies have suggested a reduced rate at 2 months (end of the intensive phase) and 6 months (end of the treatment) 9,12 while others have shown no relationship between diabetes and sputum conversion rate at the end of the secondmonth. 14,17 More data are needed to help ascertain the impact of dysglycemia on the sputum conversion rate among TB patients.…”
Section: Introductionmentioning
confidence: 99%
“…Results from previous studies on the cutoff value for sample size were not uniform, and there is no JAMA Network Open | Gastroenterology and Hepatology specific definition for this value. 7,[11][12][13][14][15][16] In this study, we predefined RCTs with sample sizes smaller than the smallest 25% samples as small-sample RCTs. Because the incidence of GC is highly variable by region and culture, with higher incidence rates overall in Asian countries, we classified RCTs into Asian and non-Asian trials based on the location of the principal investigator (PI).…”
Section: Design and Data Sourcesmentioning
confidence: 99%
“…[6,14] The WHO recommends a ve-point questionnaire on TB symptoms to screen for suspected TB cases before administering diagnostic tests such as sputum smear test, culture tests or X-rays. [15] Although recent studies on TB and DM in LMICs supported the need for DM screening among all TB patients or at least high-risk patients; [7,11,[16][17][18][19][20][21] studies on the feasibility and impact of TB screening among DM patients have showed mixed-results even in countries with a high TB burden like India. [22][23][24][25][26] Nevertheless, the WHO still recommends active screening of TB among DM patients in countries with high TB prevalence (over 100/100 000).…”
Section: Introductionmentioning
confidence: 99%
“…[6] A systematic review of studies in South Asia suggested that DM prevalence among TB patients is higher in countries with a high TB burden. [7] Moreover, TB patients with DM are more likely to have adverse treatment outcomes such as relapse or even death, and potentially show a higher risk of developing multi-drug resistant TB. [7][8][9] Uncontrolled diabetes (plasma HbA1C level ≥ 7.0%) has been identi ed in studies as a risk factor for poor TB treatment outcomes, or even treatment failure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation